2017
DOI: 10.21873/anticanres.12064
|View full text |Cite
|
Sign up to set email alerts
|

Differential Anticancer Activity of Pterostilbene Against Three Subtypes of Human Breast Cancer Cells

Abstract: Although pterostilbene, a natural analog of resveratrol, has potent antitumor activity against several human cancer types, the possible inhibitory mechanisms against subtypes of human breast cancer with different hormone receptor and human epidermal growth factor receptor 2 (HER2) status remain unknown. We investigated the anticancer activity of pterostilbene using three subtypes of breast cancer cell lines. Pterostilbene treatment exhibited a dose-dependent antiproliferative activity, with the greatest growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The oral administration of PT has been demonstrated to be an effective in vivo delivery method, achieving a higher plasma concentration than resveratrol 52 . Furthermore, the dietary supplementation of PT inhibited the growth of xenograft tumours of MDA-MB-468 triple-negative breast cancer cells 53 . Similarly, both low (56 mg/kg) and high doses (112 mg/kg) of PT inhibited the growth of xenograft tumours, with a human equivalent dose of approximately 4.6 and 9.1 mg/kg, respectively, according to Federal Drug Administration guidelines.…”
Section: Discussionmentioning
confidence: 97%
“…The oral administration of PT has been demonstrated to be an effective in vivo delivery method, achieving a higher plasma concentration than resveratrol 52 . Furthermore, the dietary supplementation of PT inhibited the growth of xenograft tumours of MDA-MB-468 triple-negative breast cancer cells 53 . Similarly, both low (56 mg/kg) and high doses (112 mg/kg) of PT inhibited the growth of xenograft tumours, with a human equivalent dose of approximately 4.6 and 9.1 mg/kg, respectively, according to Federal Drug Administration guidelines.…”
Section: Discussionmentioning
confidence: 97%
“…However, PTE is more metabolically stable and has exhibited more favorable pharmacological activities than resveratrol as its dimethyl ether structure enhances lipophilicity and membrane permeability ( 4 ). PTE has gained significant attention for its potent antioxidant, anti-inflammatory and anticarcinogenic properties ( 5 , 6 ). However, the mechanism of the inhibitory effect of PTE on tumor cells has not yet been completely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that pterostilbene is an effective antioxidant with anticancer potential, which induces cell death and exhibits anti-metastatic actions ( 16 , 30 , 32 , 34 , 37 ). Furthermore, it has been demonstrated that pterostilbene triggers apoptosis in pancreatic cancer (MIA PaCa-2 and PANC-1) ( 20 , 21 ), breast cancer (MDA-MB-468, MCF-7 and MDA-MB-231) ( 18 , 19 ), lung cancer (LCC, PC9, NCI-H460, SK-MES-1 and A549) ( 22 24 , 29 ), osteosarcoma (SOSP-9607) ( 62 ), prostate cancer (PC-3 and LNCaP) ( 25 , 26 ), leukemia (Jurkat, Hut-78, HL60, MOLT4 and K562) ( 37 40 ), colon cancer (Colo 205, HCT116 and HT29) ( 27 29 ), bladder cancer (T24) ( 30 ), hepatocellular carcinoma (HepG2) ( 35 , 36 ), gastric carcinoma (AGS) ( 31 ) and oral cancer (SAS and OECM-1) ( 32 ) cell lines. In addition, pterostilbene exhibits autophagic effects in various types of cancer ( 29 , 30 , 38 , 39 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological activities of pterostilbene mean that it may be used treat different types of diseases, including cancer, diabetes, inflammation and dyslipidemia ( 13 17 ). Studies have also indicated that pterostilbene may exhibit anticancer activity against various types of cancer, including breast ( 18 , 19 ), pancreatic ( 20 , 21 ), lung ( 22 24 ), prostate ( 25 , 26 ), colorectal ( 27 29 ), bladder ( 30 ), gastric ( 31 ) and oral cancer ( 32 34 ), as well as hepatocellular carcinoma ( 35 , 36 ) and leukemia ( 37 40 ). The results of in vitro and in vivo studies have demonstrated that pterostilbene induces apoptotic and/or autophagic cell death ( 29 , 32 , 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%